Cholangiocyte pathobiology - Banales, Jesus M.; Huebert, Robert C.; Karlsen, Tom; Strazzabosco, Mario; LaRusso, Nicholas F.; Gores, Gregory J. (Nature reviews. Gastroenterology & hepatology, 2019)
Cholangiocytes, the epithelial cells lining the intrahepatic and extrahepatic bile ducts, are highly specialized cells residing in a complex anatomic niche where they participate in bile production and homeostasis. Cholangiocytes are damaged in a variety of human diseases termed cholangiopathies, often causing advanced liver failure. The regulation of cholangiocyte transport properties is increasingly understood, as is their anatomical and functional heterogeneity along the biliary tract. Furthermore, cholangiocytes are pivotal in liver regeneration, especially when hepatocyte regeneration is compromised. The role of cholangiocytes in innate and adaptive immune responses, a critical subject relevant to immune-mediated cholangiopathies, is also emerging. Finally, reactive ductular cells are present in many cholestatic and other liver diseases. In chronic disease states, this repair response contributes to liver inflammation, fibrosis and carcinogenesis and is a subject of intense investigation. This Review highlights advances in cholangiocyte research, especially their role in development and liver regeneration, their functional and biochemical heterogeneity, their activation and involvement in inflammation and fibrosis and their engagement with the immune system. We aim to focus further attention on cholangiocyte pathobiology and the search for new disease-modifying therapies targeting the cholangiopathies. Cholangiocytes, which line the intrahepatic and extrahepatic bile ducts, are specialized cells that regulate bile production and homeostasis. Here, the authors discuss the role of cholangiocytes in development and liver regeneration, inflammation and fibrosis and their interactions with the immune system. Key points Cholangiocytes are epithelial cells lining the intrahepatic and extrahepatic bile ducts; they are heterogeneous in size and function and contribute to bile composition and flow by solute transport processes. Cholangiocytes contribute to liver regeneration, especially when hepatocyte regeneration is compromised, as is often the case in human chronic liver diseases. Cholangiocytes can become activated and participate in inflammation by secreting chemokines and cytokines and can also directly modulate the biology of myofibroblasts, the cell type responsible for collagen deposition within the liver. Cholangiocytes can become senescent and participate in the senescence-associated secretory phenotype, a cell fate also characterized by cytokine generation and release. Cholangiocytes participate in hepatic immunobiology, particularly by expressing Toll-like receptors (TLRs), contributing to immunoglobulin A (IgA) biology, and by cellular crosstalk with the innate and adaptive immune system. Cholangiocytes are damaged in a variety of human liver diseases termed the cholangiopathies, which are in need of optimized therapies and represent a current unmet need in clinical medicine.